ANALISIS EMPIRIS FAKTOR PENDORONG DAN PENGHAMBAT PADA PRAKTIK RANTAI PASOKAN HIJAU DALAM PENGGANTIAN SEDOTAN PLASTIK DI KAFE DAN RESTORAN - Muhammad Ainul Fahmi; Wina Nurfitriani; Fadila Nurfauzia; Yuki Yulyadin (PT Naureen Digital Education, 2023)
Plastic straws are often used in cafes and restaurants because they are lightweight and cheap. However, in terms of the environment, this plastic straw is considered polluting the environment because of its nature that cannot be decomposed by the environment and biosphere. Therefore, there is a need for research on empirical analysis of driving and inhibiting factors in green supply chain practices in replacing plastic straws in cafes and restaurants. In this study, a questionnaire survey was conducted at cafes and restaurants in Bandung City which then the data was processed using SEM PLS. The results of this study found that driving and inhibiting factors influence green supply chain practices in replacing plastic straws in cafes and restaurants.